Hardware-based Home VPN Server - Mohamad Adnan, Muhammad Hairy (Journal of Computing Technologies and Creative Content, 2019)
Once in the realm of the tech elite, VPN software has increasingly been used by the tech masses. This trend has most recently been driven by ISPs selling browsing histories in the US – and therefore, in effect, the user’s privacy – to the highest bidder to facilitate targeted advertising. With access to robust VPN platforms, users can more closely guard their online privacy, and access other benefits like a better level of security when using public Wi-Fi. The main pillars of a VPN are security and privacy, and these services use an encrypted tunnel to transmit your data online, with many benefits. When configuring a VPN, there are several choices for encryption protocols which can be used, and among these, one of the more popular options is currently OpenVPN which is popular for its speed, reliability, open-source and ease of use.